Evaluasi sistem informasi akuntansi pengadaan persediaan obat pada Rumah Sakit Umum Daerah Liun Kendage Tahuna - Sentinuwo, Theresya Anandhea Blessy; Budiarso, Novi; Latjandu, Lady Diana (Yayasan Widyantara Nawasena Raharja, 2025)
Liun Kendage Tahuna Regional General Hospital is a type C hospital owned by the Sangihe Islands Regency Government. This research aims to find out whether the accounting information system for the procurement of drug supplies at the Liun Kendage Tahuna Regional General Hospital is running well or not and to find out the causes of the shortage of drug supplies at the Liun Kendage Tahuna Regional General Hospital. This type of research uses qualitative research with data collection methods, namely observation, interviews and documentation. The results of this research are that the accounting information system for the procurement of drug supplies at the Liun Kendage Tahuna Regional General Hospital has not been implemented properly in accordance with the Presidential Regulation Number 12 of 2021. Where the warehouse function and the function of receiving goods are carried out by the same unit, namely in the hospital pharmacy warehouse, requests for price quotations from suppliers are not made using a letter of request for quotation, and the format of the goods requisition is the same as the format for a doctor's drug prescription. The lack of drug supplies in hospitals is caused by the level of drug use which is quite high, the functions and documents used are not appropriate, the recording system is not optimal, the drug storage warehouse does not meet standards, and drug delivery takes quite a long time.